Returning to work: Exploring the experiences of women with acute coronary syndromes - Parry, A.; Worrall-Carter, L.; Page, K.; Kuhn, L.; DiGiacomo, Michelle; Davidson, Patricia (MA Healthcare Ltd, 2007)
Aims: The aim of this study was to explore the transition experiences of Australian women in resuming paid employment after an acute coronary syndrome (ACS) event. Background: Until recently cardiovascular research has focused predominantly on men but this is changing and research exploring women’s experiences of ACS has increased. Despite knowing that many women do not resume paid employment following an ACS event, little is known about the experience of those women who do, even though it is understood that returning to the previous level of employment after an ACS event is a positive outcome. Design: An exploratory qualitative approach underpinned by naturalistic inquiry was undertaken. Methods: A purposive sample of seven women who had experienced their first ACS event 12 months ago was selected. Each woman was interviewed using a semi–structured format and their interviews were transcribed verbatim. Thematic analysis of the transcript set and conceptual mapping were employed to formulate key themes. Findings: All women (mean age 52.6 years) resumed paid employment at various stages during their recovery, but reported similar transition processes. Three key themes representing this process were identified: primary motivation; influence through guidance and support; and resuming paid employment. Conclusions: Study findings revealed that these women required substantial support from family, friends and employers, with ongoing guidance from health professionals to return to paid work. The timeframes for their return varied and some modified their roles within the workforce to enable them to return to paid work. However, formal cardiac rehabilitation did not appear to have a significant impact on these participants’ decisions to return to work. They felt that more information about this decision may have been helpful if given at the time of cardiac rehabilitation.